Synergizing Experience and Service: Their Influence on Customer Loyalty - Astuti, Rini (Indonesian Journal of Social Work, 2025)
This study aims to evaluate the influence of experiential marketing and service quality on customer loyalty. A descriptive quantitative approach was employed, using Caravan 101 restaurant as the unit of analysis and its customers as the unit of observation. The research population consisted of 5,894 customers recorded in 2018. Using the Slovin formula, a sample of 98 respondents was selected. Data were analyzed through multiple linear regression. The results indicate that experiential marketing has a partially positive and significant effect on customer loyalty, while service quality also exerts a significantly positive influence. Furthermore, when considered simultaneously, both experiential marketing and service quality demonstrate a strong and significant impact on customer loyalty